2016
DOI: 10.15621/ijphy/2016/v3i2/94904
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Efficacy of Neural Mobilization with Transcutaneous Electrical Nerve Stimulation (TENS) Versus Neural Mobilization alone for the Management of Cervical Radiculopathy

Abstract: Background: Cervical radiculopathy occurs annually in 85 out of 100,000 people. It is very disabling and interferes with the ADL of the patients. Many studies had shown the effectiveness of neural mobilization and TENS in reduction of pain and disability in patients with cervical Radiculopathy. But there are less documented studies that had shown the combined effect of neural mobilization and TENS and effectiveness of both over only neural mobilization in patients with cervical radiculopathy. Methods: 30 male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
1
8
0
1
Order By: Relevance
“…The results of our study are also in agreement with Pritam Deka,who explored that neuromobilization is effective treatment for pain and when neuromobilization and TENS combined was used then more effective results were found on cervical radiculopathy (26).…”
Section: The Results Of Routine Physiotherapy With and Without Nm Dursupporting
confidence: 91%
“…The results of our study are also in agreement with Pritam Deka,who explored that neuromobilization is effective treatment for pain and when neuromobilization and TENS combined was used then more effective results were found on cervical radiculopathy (26).…”
Section: The Results Of Routine Physiotherapy With and Without Nm Dursupporting
confidence: 91%
“…So, it was greater betterment in the experimental group as compared to the care group. The results of a study by Pritam Deka revealed that NM has fruitful effects in mitigating the pain by restoring neurodynamics properties in upper limb [ 24 ]. Robert J Nee et al study has found immediate relief of pain in arm with no evidence of harmful effects and future researches are recommended to check long term effects of NM on pain [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of current study were also similar with Pritam Deka, who explored that neuromobilization was effective treatment for pain. When neurombilization combined with TENS were used, more effective results were found on cervical radiculopathy [ 24 ]. The current study determined the results to be similar to those of Matocha MA et al who found that pain intensity decreased weekly basis as decreased in present study on 5th and 11th week but further research is needed to help clinicians in making education decision for implementing these techniques in to clinical practice [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies assessed the effects of ES combined with other intervention versus other intervention on pain intensity at rest immediately post-treatment (Albornoz-Cabello et al, 2019;Ardic et al, 2002;Azatcam et al, 2017;Chiu et al, 2005;Deka et al, 2016;Dissanayaka et al, 2016;Hendriks & Horgan, 1996;Hou et al, 2002;Kim et al, 2014;Liu et al, 2020;Nordemar & Thörner, 1981; ITT, intention-to-treat. Prabhakar & Ramteke, 2011;Tanrikut et al, 2003).…”
Section: Electrical Stimulation + Other Intervention Versus Other Int...mentioning
confidence: 99%
“…Prabhakar & Ramteke, 2011;Tanrikut et al, 2003). One meta-analysis with nine trials provided evidence of moderate quality (downgraded by inconsistency) showing that ES combined with other intervention significantly decreases pain intensity compared to other intervention immediately post-treatment (SMD −0.97; 95% CI −1.54 to −0.40) (Albornoz-Cabello et al, 2019;Ardic et al, 2002;Azatcam et al, 2017;Chiu et al, 2005;Deka et al, 2016;Hou et al, 2002;Kim et al, 2014;Liu et al, 2020;Nordemar & Thörner, 1981). Subgroup analysis according to type of NP and duration of symptoms showed significant pain reduction in NP (undetermined time) and radiculopathy (Figure 4a, Table 4).…”
Section: Electrical Stimulation + Other Intervention Versus Other Int...mentioning
confidence: 99%